ISSUES OF FORMATION OF ANTI-CORRUPTION OUTLOOK IN THE SOCIETY - R. A. Abramov (Russian Journal of Economics and Law, 2014)
Objective: to show that the formation of anti-corruption outlook is an important and vital aspect of modern society and to prove that it is more useful to prevent corruption manifestations than to combat them. Methods: the methodological basis of the research is the universal analysis and synthesis of anticorruption issues, allowing to actually or virtually divide the objects into constituent parts, and to find out which parts they consists of, what its properties and characteristics are, and to synthesize their consolidation into a single organic whole, not into a mechanical unit. Also a method of survey and statistical polls was used, including conversation, interviews, massive data collection through questionnaires and their systematization into a single report. Results: the paper studies the corruption institution as a social act, allowing to destabilize the socio-economic situation in the country as a whole. At the same time it proves the necessity to combat this phenomenon, including level impacts related to the institutional nature of the formation of a comprehensive system of the country’s sustainable development. The corruption perception by young people is explored. Basing on the conducted research, it is demonstrated that the introduction of profile and specialized courses on the existing anti-corruption state policy in the system of higher and additional education forms a new, correct outlook on the perception of corruption, which eventually should lead to the reduction of corruption level in the country. This also proves the point that prevention is more effective than struggle with corruption. Also it is proved that for the effectiveness of combating corruption and clarifying the corruption dynamics it is advisable to periodically conduct monitoring, seminars, round tables, conferences and other practical, applied measures with the participation of practitioners. Scientific novelty: the paper contains provisions on the formalization of corruption process as a part of the public discourse. It is shown that the general perception of corruption as a environmental phenomenon is formed under the influence of institutional factors. It is recommended to define the overall corruption capacity of the country with regard to social capital. Practical value: recommendations on the formation of anti-corruption outlook in the society are given. The importance on focusing measures on the regional cooperation level is proved. The consequence of the struggle is the growth of economic indicators, the extension of the scope of social capital in general. Implementation of monitoring results and other studies will contribute to the creation of a monitoring system of the corruption situation in the society in general and in education in particular, and to the reduction of the corruption level at universities, as well as improving the image of the higher education system, which can recognize the problems and solve them. Introduction of new specialized courses in educational process will form a new outlook and increase the level of knowledge in the issues of combating corruption.